Avaliação imunopatológica, pela imunofluorescência direta, do comprometimento da mucosa bucal e da pele de doenças mucocutâneas imunomediadas - Estrella, Elisa (2006)
Immune mediated mucocutaneous diseases may have several clinical presentations, leading sometimes to erroneous clinical diagnosis. Histopathological changes can be shared by a group of diseases, and therefore, the diagnosis is not always conclusive. Direct immunofluorescence is able to lead the diagnosis of immune mediated mucocutaneous diseases through characterization of antibodies in patients tissue. The objective of this study was to evaluate the efficiency of direct immunofluorescence as a complementary method to histopathological analysis, in order to come to a definitive diagnosis. Nineteen biopsies (oral mucosa and skin lesions) of thirteen patients with clinical hypotheses or histopathological reports of immune mediated mucocutaneous diseases were submited to both histopathological and direct immunofluorescence analyses. Histopathological analysis defined the diagnosis in three cases. Immunofluorescence study confirmed the diagnosis for three patients, changed the diagnosis of one and, along with clinical, laboratory and histopathological findings, allowed the diagnosis for another one. We conclude that direct immunofluorescence is an important auxiliary, and sometimes indispensable method for accurate diagnosis of immune mediated mucocutaneous diseases